Alfabetização nas escolas do campo: atuação de professoras alfabetizadoras em turmas multisseriadas - Ferla, Angelina Bigaton (2024)
Professionals in rural schools with multi-grade classes, present throughout the country, face major challenges in their pedagogical practices, especially in literacy. This research aimed to analyze the challenges and potentials of literacy practices in multi-grade classes in rural schools of a municipality in the state of Mato Grosso, Brazil. The research question was: How do teachers of rural multi-grade classes articulate and organize their literacy practices? A case study was conducted with three professionals who worked in municipal public rural schools in the school years of 2022 and 2023. These professionals taught classes with 1st and 2nd grades in the same classroom. Data collection was carried out through semi-structured interviews, based on Minayo (1994, 2014), Penna (2020), Ludke and André (1986), and Bardin (1979). The investigation discussed the current legislation on literacy and addressed theories related to the teaching of reading and writing, with contributions from theorists such as Soares (2000, 2009, 2021a, 2021b, 2022), Mortatti (2011), and Bagno (2011, 2021). The discussion on rural education was based on Azevedo and Queiroz (2010), Caldart (2012), Arroyo (2011), and Fernandes (2002). The research results were organized into four categories: "Challenges in rural literacy", "Teaching strategies for diversity", "Literacy potentialized in rural multi-grade classes", and "Formative needs based on challenges shared by rural teachers". The research results indicate the need for specific training for working in rural areas. We observed a variety of adapted approaches to the needs of the classes, but with some gaps in relation to the practices recommended in the BNCC and Magda Soares' theoretical orientation for reading and writing skills in the early years of elementary school. Additionally, some limitations of literacy practices were noted due to the use of standardized materials (textbooks). There is also an urgent need for public policies aimed at Rural Education, promoting professional appreciation and pedagogical approaches sensitive to the needs of multi-grade classes.